The Possibilities of Correlating architectural Management with Value - Yousif Tayib, Abdullah; Kawa Qadir, Akar (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
In the past decade, the management of complex architectural design processes has challenged several researchers to develop theories, methods, and techniques on how to handle the design process, most effectively to reach the maximum value. This research investigates architectural management's role in creating value in the architectural design process. The acquisition of empirical data in this particular field of research is perceived to be challenging due to the intricate combination of belief systems and scientific principles. However, there has been a notable growth in the number of models about this subject matter. The findings of a literature review indicate that there is some evidence about the impact of design management on value within the architectural design process. Several studies have made attempts to capture some aspects of project management, architectural practice, and construction management. This study aims to investigate the potential for initiating a research endeavor focused on identifying a scientific measuring approach that establishes a connection between Architectural Management and value. With a hypothesis that Architectural Management affects better value creation in the architectural design process. Due to the complex and detailed nature of design, and based on quantitative research methods and evidence. This research used two types of methods: a quantitative survey that involved distributing questionnaires to 81 architects in Sulaimani city, and an extensive review of 3 projects using an Interview as a qualitative approach, with a design quality indicator tool questionnaire (DQI) as a quantitative method for these projects. This study aims to investigate the impact of Architectural Management strategies on the perceived value of these projects. The Excel program is used for analyzing these data, and., according to the statistical analysis's findings, a significant role of Architectural Management in guiding design decisions, facilitating effective communication and coordination, and driving value creation in the architectural design process is determined. The findings provide valuable insights for architectural managers and professionals to enhance their practices and guide them in achieving successful project outcomes.